Study on Corporate Social Responsability Activities regarding Small and Medium-Sisez Entreprises in Romania (2017-2018) - ȘTEFĂNESCU, Mihnea Răzvan (Journal of Advanced Research in Management; Vol 9 No 1 (2018): JARM Volume IX Issue 1(17) Summer 2018DO - 10.14505//jarm.v9.1(17).03, 2018)
This article is meant to be an insight into the acceptance and implementation of CSR by romanian SMEs, witch is generally underestimated and poorly acknowledged, due to the fact that the internal organization of SMEs is largely informal and is mainly carried out under local or regional conditions. Social responsibility can not be seen only as a response to problems that appear during the company's development. Unless the company includes ethical concerns in it’s business strategy, social responsibility as a concept can not be integrated into it’s daily decision-making. That is why business strategy determines how the company uses the human and financial resources at its disposal to achieve its goals, and the value system of companies and stakeholders will have a profound effect on development. Measuring and evaluating CSR will not be an easy task for SMEs that do not have highly developed and reliable internal management, measurement and reporting systems (human resources, time and financial resources) and sophisticated management information systems, as the activity is difficult even for larger companies, which in many cases have these resources. In order to help companies, whether multinationals or SMEs, overcome these obstacles and have a clearer picture of CSR practices, in the paper we are going to present, we will provide not only part of what the questionnaire regarding socially responsible activities performed by the respondent companies in Romania showed, but our conclusions on it, as well.